High‐speed X‐ray imaging pixel array detector for synchrotron bunch isolation. (27th January 2016) - Philipp, Hugh T.; Tate, Mark W.; Purohit, Prafull; Shanks, Katherine S.; Weiss, Joel T.; Gruner, Sol M.
Abstract : A high‐speed pixel array detector for time‐resolved X‐ray imaging at synchrotrons has been developed. The ability to isolate single synchrotron bunches makes it ideal for time‐resolved dynamical studies. Abstract : A wide‐dynamic‐range imaging X‐ray detector designed for recording successive frames at rates up to 10 MHz is described. X‐ray imaging with frame rates of up to 6.5 MHz have been experimentally verified. The pixel design allows for up to 8–12 frames to be stored internally at high speed before readout, which occurs at a 1 kHz frame rate. An additional mode of operation allows the integration capacitors to be re‐addressed repeatedly before readout which can enhance the signal‐to‐noise ratio of cyclical processes. This detector, along with modern storage ring sources which provide short (10–100 ps) and intense X‐ray pulses at megahertz rates, opens new avenues for the study of rapid structural changes in materials. The detector consists of hybridized modules, each of which is comprised of a 500 µm‐thick silicon X‐ray sensor solder bump‐bonded, pixel by pixel, to an application‐specific integrated circuit. The format of each module is 128 × 128 pixels with a pixel pitch of 150 µm. In the prototype detector described here, the three‐side buttable modules are tiled in a 3 × 2 array with a full format of 256 × 384 pixels. The characteristics, operation, testing and application of the detector are detailed.